2013
DOI: 10.13103/jfhs.2013.28.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Predictive Models of Esherichia coli O157:H7 Growth in Paprika

Abstract: This study was carried out to develop and validate predictive models of E. coli O157:H7 growth. Growth data of E. coli O157:H7 in Paprika were collected at 12, 24, 30 and 36 o C. The population increased into 3.0 to 3.8 log10 CFU/g within 4 days, then continued to increase at a slower rate through 10 days of storage at 12 o C. The lag time (LT) and maximum specific growth rate (SGR) obtained from each primary model was then modeled as a function of temperature using Davey and square root equations, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These results demonstrated a pattern similar to the growth of E. coli O157:H7 in paprika by Yun et al. ( 2013 ), where at 10°C, bacteria were maintained at the inoculation levels and subsequently killed, and at 12°C, the number of bacteria gradually increased after 50 h. Other studies showed that E. coli O157:H7 started to grow in romaine lettuce at temperatures above 15°C (Khalil & Frank, 2010 ), and that LPD was observed from 10.5°C in meat (Tamplin et al., 2005 ). The results of the study above suggest that minimum temperatures for the growth of pathogenic E .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These results demonstrated a pattern similar to the growth of E. coli O157:H7 in paprika by Yun et al. ( 2013 ), where at 10°C, bacteria were maintained at the inoculation levels and subsequently killed, and at 12°C, the number of bacteria gradually increased after 50 h. Other studies showed that E. coli O157:H7 started to grow in romaine lettuce at temperatures above 15°C (Khalil & Frank, 2010 ), and that LPD was observed from 10.5°C in meat (Tamplin et al., 2005 ). The results of the study above suggest that minimum temperatures for the growth of pathogenic E .…”
Section: Resultssupporting
confidence: 87%
“…Ingesting food contaminated with pathogenic E . coli can cause food poisoning, which, in severe cases, can result in death (Hwang et al., 2019 ; Yun et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A f was 1.1-1.2, which was close to 1.3, and B f was 0.8-1.1, showing a value between 0.7 and 1.5, indicating a proper statistical fit. Similar results were obtained when compared to other studies (Cho et al, 2011b) on the growth prediction model of L. monocytogenes in smoked salmon (A f : 1.03-1.58, B f : 1.01-1.55), a study (Kang et al, 2010) on the growth prediction of S. aureus and Bacillus cereus in RTE foods (A f : 1.04-1.37, Bf: 0.90-1.11), the growth prediction model (Park et al, 2009) of S. aureus in green-bean sprouts provided in school meals (A f : 1.10-1.31, Bf: 0.97-1.03, MSE: 0.002-0.02), and the suitability verification value (Yun et al, 2013) of the growth prediction model for pathogenic E. coli in paprika (A f : 1.04-1.18, B f : 0.98-1.00, MRE: -1.03, -0.04). RMSE for the growth prediction model for grilled eggs, peeled quail eggs, and the whole egg liquid was 0.16, 0.26, and 0.27, respectively, showing a value that is closer to 0 than 0.300-0.5344, the RSME value measured in the study (Kim et al, 2013) on the prediction of growth of S. aureus in cheese.…”
Section: Resultsmentioning
confidence: 99%